1983
DOI: 10.1177/154079698300800102
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities Available When Severely Handicapped Students Attend Chronological Age Appropriate Regular Schools

Abstract: Article Descriptors severely handicapped students; integration; chronological age appropriate schools; least restrictive environment; parent involvement Two issues confronting those concerned with pro viding educational services to severely handicapped students are extremely important and controversial: (a) the locations in which services are provided, and (b) the nature of those services. Issues related to the loca tions in which educational and related services are pro vided and how they affect the range, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

1984
1984
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…Integration efforts should be supported by teaching appropriate social skills to severely disabled students in the context of natural, integrated environments. As Brown and his colleagues have pointed out, functional objectives cannot be taught in segregated environments because segregated environments are unlike any natural environments (Brown et al, 1983).…”
Section: Social Skills Trainingmentioning
confidence: 99%
“…Integration efforts should be supported by teaching appropriate social skills to severely disabled students in the context of natural, integrated environments. As Brown and his colleagues have pointed out, functional objectives cannot be taught in segregated environments because segregated environments are unlike any natural environments (Brown et al, 1983).…”
Section: Social Skills Trainingmentioning
confidence: 99%
“…One area of particular interest concerns the social relationships between the disabled child and nondisabled peers. Previous research has shown that a child's peer group can have a profound effect on such important factors as the disabled child's self-concept (Jones, Lavine, & Shell, 1972;Waddell, 1984), psychological well-being (Brown et al, 1983), academic performance (Corman & Gottlieb, 1978), cognitive and social development (Volpe, 1976), and many other aspects of the child's life. For these reasons, it is important to gain a better understanding of nondisabled children's perceptions of and attitudes toward their disabled peers.…”
mentioning
confidence: 98%
“…A high degree of physical and social integration can be achieved in competitive employment. Job place ments can be arranged on an individual basis and can be consistent with the concept of the natural proportion of severely disabled to nondisabled workers (Brown et al, 1983).…”
Section: Advantagesmentioning
confidence: 99%